TPE coated nylon material and preparation method thereof
Through the specific ratio of raw material composition and preparation method, the compatibility and stability problems of TPE-coated nylon materials are solved, and the comprehensive performance and production efficiency of the material are improved.
Patent Information
- Application Number
- CN202510934510.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-08
- Publication Date
- 2025-10-28
AI Technical Summary
The existing TPE-coated nylon material has poor compatibility and unstable bonding performance, which affects the product qualification rate.
TPE-coated nylon material is prepared by using a specific ratio of raw materials, including hydrogenated styrene-butadiene block copolymer, mineral oil, γ-polyglutamic acid, cetearyl glucoside, epoxidized soybean oil acrylate, anti-aging agent and filler, through extrusion and cooling in a twin-screw extruder.
This improved the compatibility and stability of TPE-coated nylon materials, enhanced bond strength, and ensured the overall performance and production efficiency of the materials.
Smart Images

Figure BDA0005487435050000061 
Figure BDA0005487435050000081
Abstract
Description
Technical Field
[0001] This application relates to the field of polymer materials technology, and in particular to a TPE-coated nylon material and its preparation method. Background Technology
[0002] Nylon, also known as polyamide fiber, is the world's first synthetic fiber. Its outstanding advantages include superior abrasion resistance compared to other fibers, as well as good heat resistance, chemical resistance, and self-lubricating properties. Therefore, nylon is widely used in machinery, chemical, and instrumentation industries. Furthermore, to improve the performance of nylon products, it needs to be coated. Current coating materials are generally thermoplastic elastomers, i.e., TPE.
[0003] TPE, also known as synthetic rubber, combines the high elasticity, aging resistance, and oil resistance of traditional cross-linked vulcanized rubber with the ease of processing and wide range of processing methods of ordinary plastics. Coating nylon with TPE can effectively improve the softness and feel of products; however, existing TPE-coated nylon materials suffer from poor compatibility and unstable adhesion, affecting product yield.
[0004] Therefore, there is an urgent need to develop a TPE-coated nylon material with high compatibility and high stability. Summary of the Invention
[0005] In order to solve at least one of the above-mentioned technical problems and develop a TPE-coated nylon material with high compatibility and high stability, this application provides a TPE-coated nylon material and its preparation method.
[0006] On the one hand, the TPE-coated nylon material provided in this application, by weight, comprises the following raw materials: 20-60 parts of hydrogenated styrene-butadiene block copolymer, 15-40 parts of mineral oil, 5-20 parts of polypropylene, 1-5 parts of γ-polyglutamic acid, 0.1-0.5 parts of cetearyl glucoside, 3-15 parts of epoxidized soybean oil acrylate, 0.05-1 part of anti-aging agent, 0.1-0.8 parts of silane coupling agent, and 15-40 parts of filler.
[0007] By adopting the above technical solution, this application uses the specific raw materials and follows a specific ratio to prepare a TPE nylon-coated material with high compatibility and stability. This application incorporates γ-polyglutamic acid and cetearyl glucoside. γ-polyglutamic acid is an excellent environmentally friendly polymer material, while cetearyl glucoside has good dispersibility. The two work together to enhance the compatibility and stability of the TPE-coated nylon material, and are themselves non-toxic and harmless. This application also incorporates epoxidized soybean oil acrylate, which improves the adhesive strength of the material.
[0008] Optionally, the mineral oil is selected from at least one of cycloalkane oils and white oils.
[0009] Optionally, the weight ratio of γ-polyglutamic acid to cetearyl glucoside is 6 to 10:1.
[0010] By adopting the above technical solution, the weight ratio of γ-polyglutamic acid to cetearyl glucoside in this application can provide good compatibility and processability, resulting in better overall performance of TPE-coated nylon materials.
[0011] Optionally, the anti-aging agent is selected from at least one of antioxidant D, antioxidant 4010, and antioxidant AW.
[0012] By adopting the above technical solution and adding anti-aging agents, oxidation and the effects of light or heat are inhibited, thereby extending the service life of the material.
[0013] Optionally, the anti-aging agent is antioxidant 4010 and antioxidant AW.
[0014] By adopting the above technical solution, the simultaneous use of antioxidant 4010 and antioxidant AW results in higher protective efficacy.
[0015] Optionally, the silane coupling agent is selected from at least one of vinyltriethoxysilane, vinyltrimethoxysilane, and vinyltri(β-methoxyethoxy)silane.
[0016] By adopting the above technical solution, the silane coupling agent of this application can improve the adhesion performance and mechanical properties of the material.
[0017] Optionally, the filler is selected from at least one of calcium carbonate, talc, mica, and silica.
[0018] Secondly, this application provides a method for preparing the above-mentioned TPE-coated nylon material, comprising the following steps: S1. The hydrogenated styrene-butadiene block copolymer, mineral oil, polypropylene, γ-polyglutamic acid, cetearyl glucoside, epoxidized soybean oil acrylate, and anti-aging agent are mixed to prepare a mixture. S2. Add silane coupling agent to the mixture, then add filler, heat and mix to obtain a premix; S3. The premixed material is fed into a twin-screw extruder for extrusion, cooled, cut and granulated, and dried to obtain TPE-coated nylon material.
[0019] By adopting the above technical solution, the preparation method used in this application is simple and convenient, ensuring the consistency and repeatability of material properties. This application employs stepwise mixing and gradual addition of raw materials, ensuring uniform distribution of each component and improving material properties.
[0020] Optionally, in step S3, the extrusion temperature is 210–230°C.
[0021] Optionally, in step S3, the cooling rate is 8-12°C per minute during the cooling process.
[0022] By adopting the above technical solution, this application uses the above extrusion temperature and cooling rate when preparing TPE-coated nylon materials, which results in high production efficiency and better material molding effect.
[0023] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The TPE nylon coated material prepared by this application using specific raw materials and in a specific ratio has high compatibility and stability.
[0024] 2. This application incorporates γ-polyglutamic acid and cetearyl glucoside, which enhances the compatibility and stability of TPE-coated nylon materials, and are themselves non-toxic and harmless.
[0025] 3. The preparation method used in this application is simple and convenient, and has high production efficiency. Detailed Implementation
[0026] The present application will be further described in detail below with reference to the embodiments.
[0027] This application designs a TPE-coated nylon material, which, by weight, comprises: 20-60 parts of hydrogenated styrene-butadiene block copolymer, 15-40 parts of mineral oil, 5-20 parts of polypropylene, 1-5 parts of γ-polyglutamic acid, 0.1-0.5 parts of cetearyl glucoside, 3-15 parts of epoxidized soybean oil acrylate, 0.05-1 part of anti-aging agent, 0.1-0.8 parts of silane coupling agent, and 15-40 parts of filler.
[0028] The method for preparing TPE-coated nylon material used in this application includes the following steps: S1. The hydrogenated styrene-butadiene block copolymer, mineral oil, polypropylene, γ-polyglutamic acid, cetearyl glucoside, epoxidized soybean oil acrylate, and anti-aging agent are mixed to prepare a mixture. S2. Add silane coupling agent to the mixture, then add filler, heat and mix to obtain a premix; S3. The premixed material is fed into a twin-screw extruder for extrusion, cooled, cut and granulated, and dried to obtain TPE-coated nylon material.
[0029] The TPE-coated nylon material proposed in this application has high compatibility and stability, which can effectively solve the technical problems of poor compatibility and stability of existing TPE-coated nylon materials, thereby improving the performance of TPE-coated nylon materials and enabling them to be better applied in production and daily life.
[0030] The raw materials used in this application are all commercially available products, as detailed below: Hydrogenated styrene-butadiene block copolymer (SEBS): Kronen G1726.
[0031] White oil: CAS: 8042-47-5.
[0032] Polypropylene: Formosa Plastics 5090T.
[0033] γ-Polyglutamic acid: CAS: 25513-46-6.
[0034] Cetearyl glucoside: CAS: 246159-33-1.
[0035] Epoxidized soybean oil acrylate: Huainan Kedi Chemical Technology Co., Ltd.
[0036] Anti-aging agent D: CAS: 135-88-6.
[0037] Anti-aging agent 4010: CAS: 101-87-1.
[0038] Anti-aging agent AW: CAS: 5891-53-2.
[0039] Vinyltriethoxysilane: CAS: 78-08-0.
[0040] Vinyltrimethoxysilane: CAS: 2768-02-7.
[0041] Calcium carbonate: CAS: 471-34-1.
[0042] Silica: CAS: 14464-46-1. Specific Implementation
[0043] Examples 1-4 Example 1 This embodiment provides a TPE-coated nylon material. By weight, the raw material composition of the highly compatible and stable TPE-coated nylon material includes: 60 parts of hydrogenated styrene-butadiene block copolymer, 15 parts of mineral oil, 15 parts of polypropylene, 5 parts of γ-polyglutamic acid, 0.5 parts of cetearyl glucoside, 15 parts of epoxidized soybean oil acrylate, 0.05 parts of anti-aging agent, 0.8 parts of silane coupling agent, and 20 parts of filler. Among them, the mineral oil is white oil; the anti-aging agent is antioxidant 4010; the silane coupling agent is vinyltriethoxysilane; and the filler is calcium carbonate.
[0044] The preparation method includes the following steps: S1. A mixture is prepared by mixing hydrogenated styrene-butadiene block copolymer, mineral oil, polypropylene, γ-polyglutamic acid, cetearyl glucoside, epoxidized soybean oil acrylate, and anti-aging agent. S2. Add silane coupling agent to the mixture, then add filler, heat and mix to obtain premix; S3. The premixed material is fed into a twin-screw extruder for extrusion at a temperature of 220°C. The material is then cooled at a rate of 10°C / min, cut and granulated, and dried to obtain TPE-coated nylon material.
[0045] Example 2 This embodiment provides a TPE-coated nylon material. By weight, the raw material composition of the highly compatible and stable TPE-coated nylon material includes: 40 parts of hydrogenated styrene-butadiene block copolymer, 28 parts of mineral oil, 12 parts of polypropylene, 3 parts of γ-polyglutamic acid, 0.3 parts of cetearyl glucoside, 9 parts of epoxidized soybean oil acrylate, 0.5 parts of anti-aging agent, 0.5 parts of silane coupling agent, and 28 parts of filler. Among them, the mineral oil is white oil; the anti-aging agent is antioxidant 4010; the silane coupling agent is vinyltriethoxysilane; and the filler is calcium carbonate.
[0046] The preparation method includes the following steps: S1. A mixture is prepared by mixing hydrogenated styrene-butadiene block copolymer, mineral oil, polypropylene, γ-polyglutamic acid, cetearyl glucoside, epoxidized soybean oil acrylate, and anti-aging agent. S2. Add silane coupling agent to the mixture, then add filler, heat and mix to obtain premix; S3. The premixed material is fed into a twin-screw extruder for extrusion at a temperature of 220°C. The material is then cooled at a rate of 10°C / min, cut and granulated, and dried to obtain TPE-coated nylon material.
[0047] Example 3 This embodiment provides a TPE-coated nylon material. By weight, the raw material composition of the highly compatible and stable TPE-coated nylon material includes: 20 parts of hydrogenated styrene-butadiene block copolymer, 35 parts of mineral oil, 5 parts of polypropylene, 1 part of γ-polyglutamic acid, 0.1 parts of cetearyl glucoside, 3 parts of epoxidized soybean oil acrylate, 1 part of anti-aging agent, 0.3 parts of silane coupling agent, and 40 parts of filler. Among them, the mineral oil is white oil; the anti-aging agent is antioxidant 4010; the silane coupling agent is vinyltriethoxysilane; and the filler is calcium carbonate.
[0048] The preparation method includes the following steps: S1. A mixture is prepared by mixing hydrogenated styrene-butadiene block copolymer, mineral oil, polypropylene, γ-polyglutamic acid, cetearyl glucoside, epoxidized soybean oil acrylate, and anti-aging agent. S2. Add silane coupling agent to the mixture, then add filler, heat and mix to obtain premix; S3. The premixed material is fed into a twin-screw extruder for extrusion at a temperature of 220°C. The material is then cooled at a rate of 10°C / min, cut and granulated, and dried to obtain TPE-coated nylon material.
[0049] Example 4 This embodiment provides a TPE-coated nylon material. By weight, the raw material composition of the highly compatible and stable TPE-coated nylon material includes: 30 parts of hydrogenated styrene-butadiene block copolymer, 40 parts of mineral oil, 20 parts of polypropylene, 2 parts of γ-polyglutamic acid, 0.2 parts of cetearyl glucoside, 5 parts of epoxidized soybean oil acrylate, 0.8 parts of anti-aging agent, 0.1 parts of silane coupling agent, and 15 parts of filler. Among them, the mineral oil is white oil; the anti-aging agent is antioxidant 4010; the silane coupling agent is vinyltriethoxysilane; and the filler is calcium carbonate.
[0050] The preparation method includes the following steps: S1. A mixture is prepared by mixing hydrogenated styrene-butadiene block copolymer, mineral oil, polypropylene, γ-polyglutamic acid, cetearyl glucoside, epoxidized soybean oil acrylate, and anti-aging agent. S2. Add silane coupling agent to the mixture, then add filler, heat and mix to obtain premix; S3. The premixed material is fed into a twin-screw extruder for extrusion at a temperature of 220°C. The material is then cooled at a rate of 10°C / min, cut and granulated, and dried to obtain TPE-coated nylon material.
[0051] Comparative Examples 1-5 Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that Comparative Example 1 does not contain γ-polyglutamic acid.
[0052] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that Comparative Example 2 does not contain cetearyl glucoside.
[0053] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that Comparative Example 3 does not contain γ-polyglutamic acid and cetearyl glucoside.
[0054] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that Comparative Example 4 does not contain epoxidized soybean oil acrylate.
[0055] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that the preparation method of Comparative Example 5 is as follows: S1. Hydrogenated styrene-butadiene block copolymer, mineral oil, polypropylene, γ-polyglutamic acid, cetearyl glucoside, epoxidized soybean oil acrylate, anti-aging agent, silane coupling agent and filler are heated and blended to obtain a premix. S2. The premixed material is fed into a twin-screw extruder for extrusion at a temperature of 220°C. The material is then cooled at a rate of 10°C / min, cut and granulated, and dried to obtain TPE-coated nylon material.
[0056] Experimental testing The tensile strength and elongation at break of TPE-coated nylon materials were tested according to GB / T 1040.2-2022 "Determination of tensile properties of plastics". According to GB / T 3512-2001 "Accelerated Aging and Heat Resistance Test of Vulcanized Rubber or Thermoplastic Rubber in Hot Air", the hot air aging properties of TPE-coated nylon materials were tested, and the retention rate of tensile strength and elongation at break after 168 h at (80±2)℃ was determined, that is, the ratio of tensile strength and elongation at break to the values before the test. Tensile strength retention rate = (tensile strength after aging test / tensile strength before aging test) × 100%; Elongation at break retention rate = (Elongation at break after aging test / Elongation at break before aging test) × 100%.
[0057] The TPE-coated nylon materials prepared in Examples 1-4 and Comparative Examples 1-5 were tested for tensile strength, elongation at break, and hot air aging properties. The test results are shown in Table 1.
[0058] Table 1 As can be seen from the test results in Table 1, the TPE-coated nylon materials prepared in Examples 1 to 4 have excellent tensile strength, elongation at break, and hot air aging properties, indicating that they have high compatibility and stability.
[0059] Comparative Example 1 does not contain γ-polyglutamic acid, and Comparative Example 2 does not contain cetearyl glucoside. The tensile strength, elongation at break, and hot air aging performance of the TPE-coated nylon materials prepared are all inferior to those of Example 2. Therefore, their compatibility and stability are also inferior to those of Example 2.
[0060] Comparative Example 3, which did not contain γ-polyglutamic acid and cetearyl glucoside, produced a TPE-coated nylon material whose properties were lower than those of Example 2, and also lower than those of Comparative Example 1 and Comparative Example 2. Therefore, it is inferred that γ-polyglutamic acid and cetearyl glucoside played a combined role.
[0061] Comparative Example 4, which does not contain epoxidized soybean oil acrylate, produced a TPE-coated nylon material that was inferior to that of Example 2 in terms of compatibility and stability.
[0062] In Comparative Example 5, the raw materials were mixed in one step, and the resulting TPE-coated nylon material showed a significant decrease in compatibility and stability.
[0063] Examples 5-13 Example 5 The difference between Example 5 and Example 2 is that in Example 5, the weight ratio of γ-polyglutamic acid to cetearyl glucoside is 8:1, and the total weight of γ-polyglutamic acid and cetearyl glucoside is 3.3 parts.
[0064] Example 6 The difference between Example 6 and Example 2 is that in Example 6, the weight ratio of γ-polyglutamic acid to cetearyl glucoside is 6:1, and the total weight of γ-polyglutamic acid and cetearyl glucoside is 3.3 parts.
[0065] Example 7 The difference between Example 7 and Example 2 is that in Example 7, the antioxidant is antioxidant D.
[0066] Example 8 The difference between Example 8 and Example 2 is that in Example 8, the antioxidant is antioxidant AW.
[0067] Example 9 The difference between Example 9 and Example 2 is that in Example 9, the antioxidant is antioxidant 4010 and antioxidant AW in a weight ratio of 1:1.
[0068] Example 10 The difference between Example 10 and Example 2 is that in Example 10, the silane coupling agent is vinyltrimethoxysilane.
[0069] Example 11 The difference between Example 11 and Example 2 is that in Example 11, the filler is silica.
[0070] Example 12 The difference between Example 12 and Example 2 is that in step S3 of Example 12, the extrusion temperature is 210°C and the cooling rate is 8°C / min.
[0071] Example 13 The difference between Example 13 and Example 2 is that in step S3 of Example 13, the extrusion temperature is 230°C and the cooling rate is 12°C / min.
[0072] The TPE-coated nylon materials prepared in Examples 5-13 were tested for tensile strength, elongation at break, and hot air aging properties. The test results are shown in Table 2.
[0073] Table 2 As can be seen from the test results in Table 2, among Examples 5, 6 and 2, the TPE-coated nylon material prepared in Example 5 has the best tensile strength, elongation at break and hot air aging performance, and therefore has the best compatibility and stability.
[0074] Among Examples 7-9 and Example 2, the TPE-coated nylon material prepared in Example 9 exhibits the best hot air aging performance. It is speculated that the simultaneous use of antioxidant 4010 and antioxidant AW can achieve a better anti-aging effect.
[0075] The TPE-coated nylon materials prepared in Examples 10, 11 and 2 have similar compatibility and stability.
[0076] Of Examples 12, 13 and 2, the TPE-coated nylon material prepared in Example 2 exhibits the best compatibility and stability.
[0077] The above are all preferred embodiments of this application, and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.
Claims
1. A TPE-coated nylon material, characterized in that, By weight, its raw material composition includes: 20-60 parts of hydrogenated styrene-butadiene block copolymer, 15-40 parts of mineral oil, 5-20 parts of polypropylene, 1-5 parts of γ-polyglutamic acid, 0.1-0.5 parts of cetearyl glucoside, 3-15 parts of epoxidized soybean oil acrylate, 0.05-1 part of anti-aging agent, 0.1-0.8 parts of silane coupling agent, and 15-40 parts of filler.
2. The TPE-coated nylon material according to claim 1, characterized in that, The mineral oil is selected from at least one of cycloalkane oil and white oil.
3. The TPE-coated nylon material according to claim 1, characterized in that, The weight ratio of γ-polyglutamic acid to cetearyl glucoside is 6~10:
1.
4. The TPE-coated nylon material according to claim 1, characterized in that, The anti-aging agent is selected from at least one of antioxidant D, antioxidant 4010, and antioxidant AW.
5. The TPE-coated nylon material according to claim 1, characterized in that, The anti-aging agents are antioxidant 4010 and antioxidant AW.
6. The TPE-coated nylon material according to claim 1, characterized in that, The silane coupling agent is selected from at least one of vinyltriethoxysilane, vinyltrimethoxysilane, and vinyltri(β-methoxyethoxy)silane.
7. The TPE-coated nylon material according to claim 1, characterized in that, The filler is selected from at least one of calcium carbonate, talc, mica, and silica.
8. A method for preparing the TPE-coated nylon material according to claim 1, characterized in that, Includes the following steps: S1. The hydrogenated styrene-butadiene block copolymer, mineral oil, polypropylene, γ-polyglutamic acid, cetearyl glucoside, epoxidized soybean oil acrylate, and anti-aging agent are mixed to prepare a mixture. S2. Add silane coupling agent to the mixture, then add filler, heat and mix to obtain a premix; S3. The premixed material is fed into a twin-screw extruder for extrusion, cooled, cut and granulated, and dried to obtain TPE-coated nylon material.
9. The method for preparing TPE-coated nylon material according to claim 8, characterized in that, In step S3, the extrusion temperature is 210~230℃.
10. The method for preparing TPE-coated nylon material according to claim 8, characterized in that, In step S3, the cooling rate is 8~12℃ / min.
